Dialética do Estado: ação política na filosofia de Éric Weil - Silva Júnior, Francisco Valdério Pereira da (2010)
This work reflects on some aspects of the political thought of Eric Weil, particularly on his Theory of the State in debate with Hegel and Marx. Marxism, understood as current political philosophy centered on the problem of liberation of the man on the historical plane, is incorporated into the project of political philosophy Weil. The Weil's Theory of the State seeks to respond to the problems of conflict between State and Society in a manner different from that which was undertaken by Marx. In the weilian thinking, the which tears apart the individual is their situation in a historical community in conflict with modern society progressive. This duality reaches its peak in the tension between community, society and state. It is here that the state is dialectically conceived as mediator and revolutionary agent for achieving freedom in the rational structure of the modern world. The Philosophy thinks about the political reality on the horizon of meaning of human action, so that the concrete political action aims the freedom of individuals, within the State, and the improving the morale of the community